(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In situ gels are systems which are applied as solutions or suspensions and are capable of undergoing rapid sol-to-gel transformation triggered by external stimulus such as temperature, pH etc. on instillation. The aim of the present investigation is to prepare and evaluate in situ gel-forming ophthalmic drug delivery system of parasympathomimetic drug carbachol, commonly known as carbamylcholine. Locust bean gum, an ophthalmic gel forming mucoadhesive polymer was chosen as polymer which undergoes instantaneous gel formation. Carbopol 934 was further incorporated as a viscosity enhancer in order to achieve the desired consistency so as to facilitate sustained drug release. The developed formulations were evaluated for clarity, pH measurement, gelling capacity, spreadability and in-vitro drug permeation study. Thus, in-situ gel based systems containing gums can be a valuable approach for ophthalmic drug delivery when compared to conventional systems.